Les compilations géographiques vénitiennes du début de l’époque moderne : savoirs politiques et politique des savoirs - Fiona Lejosne (Etudes Epistémè)
The composite form was particularly used in early modern Venetian geographical works, which are studied here in comparison and in contrast with the equivalent productions in Rome. The choice of a composite form met specific scientific needs: compiling textual material allowed to bring together geographical knowledge that was, at the time, abundant, plural, and heterogeneous. But the political dimension of geography was indisputable and should also be taken into account. The composite nature of some of the geographical works published in Venice – as well as the scarcity of this form amongst Roman books – is tied to the political scope of such publications. Venetian compilations publicised Venetian travels and, at the same time, promoted the ability of Venice to take advantage of its networks in order to gain control over the circulation of knowledge.